Comparison between moderate-load and high-load exercises in the rehabilitation of runners with Achilles tendinopathy: Protocol for a blind randomized controlled trial - Magno Jackson Moreno; Anne-Sofie Agergaard; Mateus Antônio Albuquerque Costa; Rene Brüggebusch Svensson; S. Peter Magnusson; Rodrigo Scattone Silva (PLoS ONE, 2026)
Background Achilles tendinopathy is one of the most frequent conditions affecting runners. Exercise-based interventions are the main treatment options for Achilles tendinopathy; however, the ideal exercise dosage remains unknown. Objective The objective of this study is to investigate the effects of a moderate-load exercise intervention compared to a high-load exercise intervention in runners with Achilles tendinopathy in terms of pain, symptom severity, quality of life, muscle strength, and function. Methods Sixty amateur runners will be randomly allocated to one of two groups: high-load exercise group (HLG) and moderate-load exercise group (MLG). The HLG will start the treatment with calf exercises with 55% of 1 repetition maximum (1RM) and progressively increase the exercise load in 12 weeks to 90% 1RM. The MLG will perform exercises with 55% 1RM during the 12 weeks of intervention. The RM load will be reassessed every 2 weeks, and the total training volume (total repetitions and tendon time under tension per week) will be the same in both groups. Both groups will also perform strengthening exercises for the quadriceps and gluteal muscles. The primary outcome will be symptom severity (Victorian Institute of Sport Assessment−Achilles), which will be evaluated at baseline, at week 6, at week 12 (end of intervention), and 6 months after the intervention. Pain will be evaluated using the visual analogue scale during the same time points. Secondary outcomes will include peak isometric strength of ankle, knee, and hip muscles, function of plantar flexor muscles, quality of life, and perception of improvement. Results will be analyzed under the intention-to-treat principle using generalized estimating equations (GEE) and Bonferroni-adjusted post hoc tests. Discussion This will be the first randomized controlled trial comparing high-load exercises versus moderate-load exercises in individuals with Achilles tendinopathy applying equal training volume. Trial registration number RBR-4vwy5xj